Peace at the Last: A Christian Theology of Last Things - Nalkara, Benny (Asian Horizons, 2011)
Colm McKeating, Peace at the Last: A Christian Theology of Last Things, Quezon City: Claretian Publications, 2009. Pages xvi+282, ISBN: 978971-0511-30-3